A Longitudinal Analysis of Handwashing and Mask-Wearing During COVID-19 - Croucher, Stephen; Ashwell, Douglas; Murray, Niki; Condon, Shawn Michael; Fletcher, Phoebe (Frontiers in Communication, 2021)
The COVID-19 pandemic has seen health preventive behaviours to prevent spread of the virus become highly politicised in the United States. A clear division exists between Democrats favouring health preventive measures and Republicans often defying such measures. Amid increasing fear of the virus, the 2020 U.S. presidential election became central to how the pandemic should be managed. This longitudinal study examines whether the frequency of handwashing and mask-wearing changed after the U.S. election. The study further explores whether political partisanship played a part in the change. Results show that handwashing and mask-wearing increased among Democrats after the election. However, Republican’s use of masks and handwashing decreased. These results are explained in terms of loyalty to outgoing President Trump among Republicans and renewed feelings of efficacy among Democrats.